Bid Bazaar: A Comprehensive and Innovative E-Commerce Platform Featuring Real-Time Online Auctions and Seamless Shopping Experience - Suryawanshi, Mayank; Sachdeva, Mahek; Bhusankar, Mohit; Yadav, Manoj (International Journal of Computer Sciences and Engineering, 2025)
Bid bazar is web application which will help the users to buy and sell the products. The system that holds the various products on a website and server sellers and bidders accordingly. And it is designed to allow users to set up their products for auctions and bidders to register and bid for different types of products that are available. This is a best method for buying and selling the products and services. And it helps the customers to buy and sell the products at reasonable price. There are some existing applications that allows users forbidding but the product is not available in your local area, you cannot do inspection of the product that you are going to buy. By online auction application user will be able to bid for product that is available in this local area.